Theoretical and Experimental Insights of Benzimidazole Catalyzed by the Epoxy–Acrylic Acid Reaction - Muhammad Jawwad Saif; Fazal-ur-Rehman; Shazia Abrar; Arruje Hameed; Nazeran Idrees; Muhammad Asif (Molecules, 2022)
This study focuses on the experimental and molecular-level investigation of epoxy acrylate formation. Epoxy acrylate vinyl ester resin was prepared by a reaction of diglycidyl ether of bisphenol-A-based epoxy resin and acrylic acid, using benzimidazole as a catalyst. It was confirmed that benzimidazole can effectively catalyze this reaction. FTIR analysis of the product revealed a simple addition esterification reaction between the epoxide group and carboxylic group of acrylic acid excluding the side reactions (e.g., etherification). DFT computational studies were performed to theoretically explore the insights of reaction mechanisms. The calculations revealed that the benzimidazole-catalyzed reaction dominates the uncatalyzed reaction. A comparison of calculated activation energies showed that concerted mechanisms are less significant in such reactions owing to their high activation barriers.